Santai Technology : Plowefer Machine / Nur Najihah Iman Mohd Sanusi...[et al.] - Abdul Jalil, Aliff Johan; Ruslib, Mohd Rasydan; Baharudin, Muhammad Haziq; Mohd Sanusi, Nur Najihah Iman (2019)
Santai Technolgy is a small business with a purpose that is to ease every Malaysian farmer with their farming work. This company is trading type where it improvises the product to give such a big impact to community for a better living